Psychological Impact From Covid-19 Among Universiti Students: Risk Factor UTHM Students - Mohamad, Andi Nurizzah; Che Him, Norziha (Enhanced Knowledge in Sciences and Technology, 2023)
In general, In the 1960s and 1970s, psychology underwent a conceptual change, adopting a strict, scientific, lab-based approach with consequences for memory, perception, cognitive development, mental illness, and more. Generally, psychology is to describe a behaviour or way of thinking. Hence, the objective in this study is to determine the variety of psychological effects during Covid-19 among student university and analyse expected feeling that can impact psychological impact student during Covid-19 by using Chi-Square and Logistic regression method. Total of the respondents is 121 were selected via convenience sampling. Pilot test had been done and Cronbach alpha value is 0.7. Female are more likely to get variety of psychological impact because frequency female are more than male. Results were analysed by using Cross tabulation, Chi-square test and Binary Logistic Regression. Conclude that, female are more have variety psychological effect than females and students are also got the impact of psychology during Covid-19 . Lastly, during pandemic students are more likely preferred indoor activities than outdoor activities.